Model Project Based Learning Meningkatkan Kreativitas dan Keterampilan Berwirausaha Siswa Saat PJJ - Zuniarti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
The purpose of the research is to find out how is the process of implementing the project based learning model in increasing creativity and skills in making student business products, how are the results of increasing students' creativity and skills in making business products through a project based learning model in the lesson of creative products and entrepreneurship for class XII culinary 4 SMKN 1 Sewon 2020/2021. This research is a classroom action research (CAR) with a project based learning model. The research subjects were students of class XII Catering 4 at SMK Negeri 1 Sewon, totaling 31 students. Implementation from July to October 2020, consists of 3 cycles, with the stages: